Plasticity and coordination of branch and leaf traits in Ulmus pumila along a precipitation gradient - Zhao, Yuhang; Gong, Xuewei; Ning, Qiurui; Zhang, Chi; Duan, Chunyang; Hao, Guangyou (Ying yong sheng tai xue bao, 2023)
We compared branch and leaf functional traits of trees inhabiting different climatic zones (sub-humid, dry sub-humid and semi-arid zones), aiming to investigate the role of trait plasticity and coordination in tree acclimation to different water conditions. The results showed that leaf drought stress of increased significantly from sub-humid to semi-arid climatic zones, as indicated by a 66.5% reduction in leaf midday water potential. In the sub-humid zone with less severe drought stress, had higher stomatal density, thinner leaves, larger average vessel diameter, pit aperture area and membrane area, which could ensure the higher potential water acquisition. With the increases of drought stress in dry sub-humid and semi-arid zones, leaf mass per area and tissue density increased, and the pit aperture area and membrane area decreased, indicating stronger drought tolerance. Across different climatic zones, the vessel and pit structural characteristics were strongly coordinated, while a trade-off between xylem t